New concepts in opioid analgesia. (3rd October 2018) - Stein, Christoph
ABSTRACT: Introduction : Opioids are the oldest and most potent drugs for the treatment of severe pain, but they are burdened by detrimental side effects such as respiratory depression, addiction, sedation, nausea, and constipation. Their clinical application is undisputed in acute (e.g. perioperative) and cancer pain, but their long-term use in chronic pain has met increasing scrutiny and has contributed to the current 'opioid crisis.' Areas covered : This article reviews pharmacological principles and research strategies aiming at novel opioids with reduced side effects. Basic mechanisms underlying pain, opioid analgesia, and other opioid actions are outlined. To illustrate the clinical situation and medical needs, plasticity of opioid receptors, intracellular signaling pathways, endogenous and exogenous opioid receptor ligands, central and peripheral sites of analgesic, and side effects are discussed. Expert opinion : The epidemic of opioid misuse has taught us that there is a lack of fundamental knowledge about the characteristics and management of chronic pain, that conflicts of interest and validity of models must be considered in the context of drug development, and that novel analgesics with less abuse liability are badly needed. Currently, the most promising perspectives appear to be augmenting endogenous opioid actions and selectively targeting pathological conformations of peripheral opioid receptors.